Text and Instruction Necessary for the Facilitation of EFL Reader’s Predictive Inference Generation - Masahiro MAEDA (Association of Language Teachers in Southeast Asia (ALTSA), 2023)
Inference generation is necessary for reading to understand stories. However, it may be difficult for English as a Foreign Language (EFL) readers to generate inferences owing to their limited cognitive resources that are mostly used in lower-level processing such as lexical and syntactical analysis. Predictive inference, which facilitates readers’ context processing and construction of a situational model, can be challenging for EFL readers to produce during reading. This study focuses on textual conditions and teacher’s task instructions to suggest the appropriate text choices and task instructions to help EFL readers produce predictive inferences. Two story versions (High-predictability Target vs. Control) and two different instructions (Predict the end of the story vs. Memorize the names of characters) were compared using recall rates. The findings indicated that the combination of a high-predictability target story with instructions to predict the end of the story would be the most effective pair for predictive inference.